PENGEMBANGAN MODUL BUDAYA POSITIF BERBASIS NILAI-NILAI KEPEMIMPINAN SYEIKH ASNAWI CARINGIN DI SDN SE-KECAMATAN PATIA KABUPATEN PANDEGLANG - Zainudin, Ikhwan (ATTA`DIB, 2025)
This research was motivated by the condition of elementary school students in Patia District, Pandeglang Regency who do not yet understand, let alone implement, local wisdom values in learning at school and in everyday life. Seeing these conditions, the author is interested in developing a positive cultural module containing local wisdom content by emulating the characteristics of one of Banten's ulama figures, namely Sheikh Asnawi Caringin or more familiarly called Mama Caringin. This research aims to instill the local wisdom values that Mama Caringin possessed during her lifetime, so that students are able to adopt and even implement them in their daily lives. The method used in this research is Research and Development (R&D). The results of research conducted by the author on fifth grade students in 15 elementary schools in Patia subdistrict, Pandeglang Regency show that from the results of limited trials and field trials, it turns out that the module presented by the author in learning activities in fifth grade elementary schools in Patia Subdistrict, Pandeglang Regency is feasible. used. This is evident from student learning results which show understanding of the material presented in the positive culture module based on local wisdom.